Artificial Intelligence in Dentistry - A Review - G L Gokul1 , Balaji Ganesh S2 , K. R. Don3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Artificial Intelligence (AI) is a breakthrough in the field of technology which is rapidly progressing andhas captivated the minds of researchers across the globe. Ever since its discovery, dentistry has witnessedsome of the exceptional achievements. Hence, this technology as the future of dentistry is abutting theimplementation of its application. While, in no ways, AI can replace the role of the dentist, it is of primeimportance to be aware of the possibilities to integrate this technology in the future of a gratifying andsuccessful practice. The aim of this review is to analyse the role and applications of artificial intelligencein dentistry. The field of artificial intelligence has transformed medicine and dentistry in several ways. AIcan only assist the clinician in performing the tasks efficiently, but in no way, the intellect of the humanknowledge skill and treatment planning